Iatrogenic Superior Vena Cava Syndrome after Cardiopulmonary Bypass Diagnosed by Intraoperative Echocardiography. (18th August 2020) - Ellison, Matthew B.; Statler, Alex; Henrickson, Roy E.; Graff, Julia; Sloyer, Daniel; Abbas Khan, Mir Ali; Hayanga, Heather K.; Ellison, Pavithra R.
Abstract : A 73-year-old female patient presented for mitral valve replacement and coronary artery bypass grafting secondary to multivessel coronary disease and severe mitral valve regurgitation with moderate stenosis. After bypass, the patient developed refractory hypotension with decreased biventricular volume and elevated central venous pressure (CVP). Transesophageal echocardiography (TEE) was utilized to make the diagnosis of acute intraoperative superior vena cava (SVC) syndrome. The SVC cannulation site was revised, resulting in resolution of the hypotension and a decrease in the CVP. Intraoperative TEE was vital in recognizing, managing, and ultimately repairing the acute intraoperative SVC stenosis.